Development and Validation of the Disability Index Among Older Adults. Issue 1 (10th March 2022) - Zhang, Xuxi; Lin, Lizi; Sun, Xinying; Lei, Xiaoyan; Liu, Gordon G; Raat, Hein; Zeng, Yi
Abstract: Background: With the rapid population aging, the challenge to provide care for disabled older adults is becoming bigger. This study aims to develop the Disability Index (DI) to assess disability to indicate care needs, and we evaluated the reliability and validity of the DI among older adults aged 65–105. Methods: A total of 12 559 older adults (54.0% women; mean age = 84.3; SD = 11.2) from 22 provinces in China were investigated in 2017–2018. We developed the 21-item DI covering 4 subdomains, including Activities of Daily Living (ADL), Instrumental Activities of Daily Living (IADL), physical performance, and cognitive function. Cronbach's alpha was used to determine internal consistency. The convergent and divergent validity were assessed by Spearman rank order correlation coefficients and Pearson correlation coefficients. The known-group validity was assessed by Mann–Whitney U tests. The concurrent validity was assessed by the area under the receiver operating characteristic curve (AUC). Results: In the total sample, the internal consistency of the full DI and its subdomains were satisfactory with Cronbach's alpha ≥0.70; the convergent and divergent validity of the 4 subdomains were supported by all the alternative measures; the known-group validity of the full DI and its subdomains were supported by clear discriminative ability; and the concurrent validity of the full DI was supported with all the AUCs ≥0.70. The reliability and validity of the full DI and its subdomains were additionally supported by age subgroups and sex subgroups. Conclusions: The DI is a reliable and valid instrument to assess disability status among older adults.